GENETIC DIVERSITY OF Lactobacillus spp. OF NATURAL ETHAWAH GOAT MILK-FERMENTED WAS DETERMINED BY USING 16SRDNA WITH DDGE ANALYSIS - Nur Kusmiyati; Nur Hidayat; Fatchiyah Fatchiyah (The East Java Biological Society, 2013)
phoresis (DGGE) analysis. Goat and bovine (as negative control) milk naturally fermented among 24hour until 6 days. Morphological and biochemistry of bacteria were characterized by standard methods. The total DNA of bacteria were isolated using alkali lysis, PCR amplification was carried out using 3 pairs of specific primers, DNA-amplified using DGGE and then to determine the relationship among Lactobacteria using NTsys package software V2.0. Phenotypical and biochemical study showed that the 11 strains are belonging to genus Lactobacillus. The dendogram results show all of isolates had similarity characters with genus Lactobacillus around 56-76%. According to morphological and DDGE profiles, we were identified that bacteria isolate of goat milk-fermented are K1A, and K3A are L. casei, and bacteria isolate K3B is L. plantarum.